A 10-Year Retrospective before-and-after Study of Lipedema Surgery: Patient-Reported Lipedema-Associated Symptom Improvement after Multistage Liposuction. Issue 3 (March 2022) - Kruppa, Philipp; Georgiou, Iakovos; Schmidt, Jeremias; Infanger, Manfred; Ghods, Mojtaba
Abstract : Background: Despite an increasing demand for surgical treatment of lipedema, the evidence for liposuction is still limited. Little is known about the influence of disease stage, patient age, body mass index, or existing comorbidities on clinical outcomes. It was hypothesized that younger patients with lower body mass index and stage would report better results. Methods: This retrospective, single-center, noncomparative study included lipedema patients who underwent liposuction between July of 2009 and July of 2019. After a minimum of 6 months since the last surgery, all patients completed a disease-related questionnaire. The primary endpoint was the need for complex decongestive therapy based on a composite score. Secondary endpoints were the severity of disease-related complaints measured on a visual analogue scale. Results: One hundred six patients underwent a total of 298 large-volume liposuctions (mean lipoaspirate, 6355 ± 2797 ml). After a median follow-up of 20 months, a median complex decongestive therapy score reduction of 37.5 percent (interquartile range, 0 to 88.8 percent; p < 0.0001) was observed. An improvement in lipedema-associated symptoms was also observed ( p < 0.0001). The percentage reduction in complex decongestive therapy scores was greater in patients with a body mass index less than or equal to 35 kg/m 2 ( p < 0.0001) and in stage I and II patients ( p = 0.0019). Conclusion: Liposuction reduces the severity of symptoms and the need for conservative treatment in lipedema patients, especially if it is performed in patients with a body mass index below 35 kg/m 2 at an early stage of the disease. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.